Office finances made easy : a get-started guide to budgets, purchasing, and financial statements - Finney, Robert G. (AMACOM, 2000)
An overview of the basics of business finances and "numbers". Targeted at junior-level employees, it covers: budgeting - defining and planning budgets, dealing with uncertainty, generating the final budget, and getting it approved; purchasing - defining requirements, specifying and estimating, gathering bids, making the lease-or-buy decision, getting the lowest price (for computers, maintenance services, temps, printing); and financial statement analysis - understanding the basic documents and concepts, including income statements, the balance sheet, cash flow, and profit and loss